Epigenetic mechanisms linking atherosclerosis to ischemic stroke: insights from DNA methylation and transcriptome integration - Ding, Binrong; Wang, Yiqun; Li, Junfeng; Zhang, Xuewei; Wan, Zhengqing; Wang, Hao (Frontiers in Genetics, 2025)
BackgroundIschemic stroke (IS) is a major cause of mortality and disability, with atherosclerosis (AS) as a primary risk factor. DNA methylation plays a critical role in AS development, but its regulatory mechanisms remain unclear. This study aims to investigate the epigenetic regulatory mechanisms linking AS and IS by integrating DNA methylation and transcriptome data from public databases.MethodsThis study integrated DNA methylation (GSE46394) and transcriptome data (GSE111782 and GSE162955) from public databases to investigate the molecular mechanisms linking AS and IS. Differentially methylated CpG positions (DMPs) and differentially expressed genes (DEGs) were identified (p < 0.05). Subsequent gene annotation and enrichment analyses were performed to uncover potential molecular mechanisms underlying the relationship between AS and IS.ResultsA total of 5,396 consistent DMPs were identified in aortic and carotid atherosclerotic lesions, with enriched pathways such as MAPK signaling and Hippo signaling. Transcriptome analysis revealed 1,147 DEGs in AS plaques and 1,321 DEGs in IS brain tissues, enriched in pathways including neuroactive ligand-receptor interactions, calcium signaling, and vascular smooth muscle contraction. Overlapping analyses identified shared processes like actin filament polymerization, cell migration, and MAPK cascade regulation, as well as pathways such as adrenergic signaling, and apelin signaling.ConclusionThis study highlights the pivotal role of epigenetic regulation in AS and IS, uncovering key pathways and molecular processes involved in their progression. Future studies should validate these findings in larger cohorts and integrate multi-omics approaches for a comprehensive understanding.